2020
DOI: 10.3390/jcm9020498
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coronavirus Outbreak in Wuhan, China, 2020: Intense Surveillance Is Vital for Preventing Sustained Transmission in New Locations

Abstract: The outbreak of pneumonia originating in Wuhan, China, has generated 24,500 confirmed cases, including 492 deaths, as of 5 February 2020. The virus (2019-nCoV) has spread elsewhere in China and to 24 countries, including South Korea, Thailand, Japan and USA. Fortunately, there has only been limited human-to-human transmission outside of China. Here, we assess the risk of sustained transmission whenever the coronavirus arrives in other countries. Data describing the times from symptom onset to hospitalisation f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
172
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 24 publications
3
172
0
4
Order By: Relevance
“…While countermeasures to prevent epidemic spread require the sort of strong political decisions that resulted in strong movement restrictions, our study indicated that the delay to a major epidemic in countries other than China (using Japan as an example) was unfortunately minimal. While the complete lockdown of Wuhan, Wenzhou, and Shenzhen likely helped reduce case incidence outside of these cities, migration from other cities in China could still contribute to the spread of infection locally and internationally [24][25][26]. To quantify the epidemiological impact for the entire course of the epidemic more precisely, a more detailed analysis using dynamic datasets, e.g., airline passenger data, should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While countermeasures to prevent epidemic spread require the sort of strong political decisions that resulted in strong movement restrictions, our study indicated that the delay to a major epidemic in countries other than China (using Japan as an example) was unfortunately minimal. While the complete lockdown of Wuhan, Wenzhou, and Shenzhen likely helped reduce case incidence outside of these cities, migration from other cities in China could still contribute to the spread of infection locally and internationally [24][25][26]. To quantify the epidemiological impact for the entire course of the epidemic more precisely, a more detailed analysis using dynamic datasets, e.g., airline passenger data, should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Cases have also been reported from other Chinese provinces and with > 300 cases outside China. Currently, the person-to-person transmission is considered the main mode of transmission and rigorous surveillance in other countries is required to prevent further global expansion of the outbreak (Thompson, 2020, Imai et al, 2020. Resolving the exact mechanism of the initial transmission events is crucial in preventing this type of outbreaks from occurring.…”
Section: Main Textmentioning
confidence: 99%
“…Resolving the outbreak in this situation is extremely challenging due to the high media interest and political pressure. The prevention of expansion of the outbreak requires other measures (Thompson, 2020). Often during the outbreak investigations, the information flow between health and food control authorities faces unplanned walls.…”
Section: Main Textmentioning
confidence: 99%
“…1 They have enveloped virions that appear as round or oval, often polymorphous, with a diameter of 60-140nm. 2 It is widely distributed in human and other mammals, and its genome is more distant from severe acute respiratory syndrome coronavirus (SARS CoV) 3,4 and Middle East respiratory syndrome coronavirus (MERS CoV) 5,6 . Since December 2019, a large number of patients infected with COVID-19 have been reported in Wuhan, Hubei Province.…”
Section: Introductionmentioning
confidence: 99%